ANALYSIS OF QUALITY OF SERVICE OF MOBILE AD-HOC NETWORKS USING DIFFERENT QUEUING POLICIES - Olanrewaju, O. M.; Adebayo, I. O.; Adebiyi, Faith O. (FUDMA Journal of Sciences, 2023)
A wireless Ad-hoc network consists of wireless nodes communicating without the need for a centralized administration; all nodes potentially contribute to the routing process. The fragile and temporary nature of mobile ad-hoc connectivity makes quality of service a crucial issue. In this paper, mobile ad-hoc wireless network of 25 nodes were modelled using Riverbed Modeller for the purpose of evaluating quality of service performance of different queuing policies. The simulation results of four different scenarios of wireless ad hoc networks were reported. The quality of service of the different queuing policies were evaluated in terms of traffic received, network delay and throughput. In this simulation environment, priority queue and Weighted Fair Queuing (WFQ) scheduling performs better than First In First Out (FIFO) and custom queuing scheduling in terms of traffic received. On the other hand, Wireless Local Area Network (WLAN) delay in FIFO and Custom queuing scheduling is less than that of Priority queuing scheduling. The research concludes that the type of application in focus should be part of determinant factor for the choice of queuing mechanism. According to the result, FIFO is faster for applications that have fairly close time priority while time sensitive applications have to consider Priority queue or weighted queue scheduling.